Moradores em Situação de Rua: uma etnografia urbana da cidade de Cascavel/PR - Giacomelli, Eliane Terezinha (2021)
The reality that people live or remain on the streets is not only a Brazilian, but a worldwide phenomenon, with greater visibility in large cities and it is considered a public order problem. In this research, we sought to know the daily lives of homeless people with the objectives of: (i) analyzing the life stories of homeless people and their relationships of social vulnerability; (ii) carry out a comprehensive and interpretive description of their life stories, identifying the reasons that led them to live on the street; (iii) understand the meanings of the experience of living on the street; (iv) apprehend experiences of social vulnerability and violence from the point of view of homeless people; (v) identify their demands for proposing social policies. This is a qualitative research, of an ethnographic and photoethnographic type, guided by a phenomenological gaze immersed in live and be in the streets from August 2020 to March 2021 in the city of Cascavel / PR, Brazil. For data collection, the places used and inhabited by this population, paths taken and life stories were mapped and registered. It should be noted that such ways of living differ even in the choice and use of equipment and services available to the homeless population. The results of this research reveal that the relationship they produce in living on the streets is based on a normative and standardized essence of an excluding, “identitary” and predictable model.